2009
DOI: 10.1111/j.1600-0587.2009.05888.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape fragmentation influences winter body mass of roe deer

Abstract: Body size of large herbivores is a crucial life history variable influencing individual fitness‐related traits. While the importance of this parameter in determining temporal trends in population dynamics is well established, much less information is available on spatial variation in body size at a local infra‐population scale. The relatively recent increase in landscape fragmentation over the last century has lead to substantial spatial heterogeneity in habitat quality across much of the modern agricultural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 60 publications
(92 reference statements)
4
82
0
Order By: Relevance
“…This flexibility may confer nutritional advantages to individuals living in fragmented landscapes when their native food resources become scarce or decrease in quality, such as in non-mast winters and in summer drought. This may constitute a mechanistic explanation for the recent observation that roe deer body mass increases along a gradient of habitat fragmentation in our study site, with the heaviest deer occurring in the most open sectors and the lightest in the strict forest environment (Hewison et al 2009). However, the nutritional benefits of foraging in open habitats may be counterbalanced by higher predation risk when cover is scarce (Benhaiem et al 2008).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This flexibility may confer nutritional advantages to individuals living in fragmented landscapes when their native food resources become scarce or decrease in quality, such as in non-mast winters and in summer drought. This may constitute a mechanistic explanation for the recent observation that roe deer body mass increases along a gradient of habitat fragmentation in our study site, with the heaviest deer occurring in the most open sectors and the lightest in the strict forest environment (Hewison et al 2009). However, the nutritional benefits of foraging in open habitats may be counterbalanced by higher predation risk when cover is scarce (Benhaiem et al 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Within populations, individuals may show plastic behaviours in response to landscape heterogeneity in terms of space use (Tufto et al 1996;Lovari and San José 1997;Lamberti et al 2006;Said et al 2009), group size Jepsen and Topping 2004), activity rhythms and diet composition (Barancekova 2004). Furthermore, in agricultural landscapes, both roe deer body mass and faecal indicators of diet quality have been shown to increase along a gradient of forest fragmentation, suggesting that individuals with access to cultivated food resources obtain diets of better nutritional quality than those living in remnant forest (Hewison et al 2009). …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The human population occurs in small villages and farms connected by an extensive road network. Within this study site, at the scale of a deer's home range, the local landscape structure is spatially variable in terms of the degree of forestation and the type of agricultural activity (see Hewison et al 2001Hewison et al , 2009 for a more detailed description).…”
Section: Study Sitementioning
confidence: 99%
“…This host species, originally considered forest dwelling, relatively recently expanded its range into modern agricultural landscapes (Hewison et al 2001), thus gaining access to highly nutritious cultivated meadows and crops (Hewison et al 2009). However, previous work has indicated that human disturbance and restriction in home range has resulted in increased parasite load of this Cervidae (Lutz and Kierdorf 1997).…”
Section: Introductionmentioning
confidence: 99%